An integrated molecular characterization and simulation study of chain length effects on PFAS adsorption at hydrophobic interfaces - Gbassey S.A. Otémé; Rebekah Finster-Goel; Siavash Mohamadi; Juan Moya; Tashfia M. Mohona; Ning Dai; Zhijiang Ye; Prathima C. Nalam (Water Research, 2026)

Cloudburst or hybrid phenomenon? Dissecting the Dharali flood disaster of 2025 - Gopika Vijayalekshmi; N. K. Goel; Manohar Arora; M. L. Sharma; R. Unni Narayanan; R. K. Vishnoi (Hydrological Sciences Journal, 2026)

Anti-Obesity Effect of Probiotic Carrot Nectar Incorporated with L. Plantarum MCC5231 - Aditi Goel; Md Touseef Khan; S. P. Muthukumar; Attar Singh Chauhan; Jyoti Prakash Tamang; Prakash. M. Halami (Probiotics and Antimicrobial Proteins, 2026)

Effect of sex, leg dominance, and task on knee cartilage and anterior cruciate ligament biomechanics during single-leg landings-a pilot study - Sara Sadeqi; Grant E. Norte; Amanda Murray; David M. Dueber; Michael D. Toland; Deniz U. Erbulut; Vijay K. Goel (Next Research, 2026)

The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Short-range monsoon rainfall forecasting using multi-model ensembles and analysis of threshold-based rainfall verification - Suman Gurjar; N. K. Goel; Manohar Arora; M. K. Goel (Theoretical and Applied Climatology, 2026)

Enzymatic assay based platform for the chiral purity assessment of cathepsin-cleavable antibody-drug conjugate linker-drugs - Meenakshi Goel; Sreya Sarkar; Christopher M. Crittenden; Eileen Zhao; Bingchuan Wei; Bifan Chen; Lance Cadang (Analytica Chimica Acta, 2026)

A review on pyrimidine-based pharmacophore as a template for the development of hybrid drugs with anticancer potential - Shivam Sharma; M. Arockia Babu; Roshan Kumar; Thakur Gurjeet Singh; Ashish Ranjan Dwivedi; Gazanfar Ahmad; Kapil Kumar Goel; Bhupinder Kumar (Molecular Diversity, 2025)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

Performance evaluation of biomass chemical looping gasification in a fluidized bed reactor using industrial waste as oxygen carrier - Avishek Goel; Fabiola Panitz; Elyas M. Moghaddam; Jochen Ströhle; Bernd Epple; Chao He; Jukka Konttinen (Bioresource Technology, 2025)

Spatial Heterogeneity in Health Risk Assessment of Heavy Metals During North-East Monsoon and South-West Monsoon over India - Martina Rani; Sakshi Ahlawat; N. Vijayan; Lokesh Yadav; Tirthankar Banerjee; Abhijeet Chatterjee; Manpreet Singh Bhatti; Trupti Das; Amit Dhir; Sangita Goel; Altaf Husain Khan; Ravindra Khaiwal; et al. (Aerosol Science and Engineering, 2025)

Growth and anatoxin-a production of Microcoleus (Cyanobacteria) strains from streams in California, USA - Sydney M. Brown; Joanna R. Blaszczak; Robert K. Shriver; R.Christian Jones; Abeer Sohrab; Ramesh Goel; Gregory L. Boyer; Bofan Wei; Kalina M. Manoylov; T.Reid Nelson; Jordan M. Zabrecky; Rosalina Stancheva (Harmful Algae, 2025)

Innovations in tannery wastewater management: a review of zero liquid discharge technology - A. Pundir; M. S. Thakur; B. Goel; Radha; A. Kumar; S. Prakash; M. Thakur; M. Kumar (International Journal of Environmental Science and Technology, 2025)

Micelle-engineered nanoplatforms for precision oncology - Wei Gao; Ashkan Bigham; Matineh Ghomi; Ali Zarrabi; Navid Rabiee; Mohammad Reza Saeb; Yavuz Nuri Ertas; Arul Goel; Esmaeel Sharifi; Milad Ashrafizadeh; Gautam Sethi; Murtaza M. Tambuwala; et al. (Chemical Engineering Journal, 2024)

Study of pathogenic T-helper cell subsets in Asian Indian patients with Takayasu arteritis - P. M. Punithavathy; Ramesh Babu Telugu; Vinay Murahari Rao; Savit B. Prabhu; Jayakanthan Kabeerdoss; Chanduni Syed; George Joseph; Debashish Danda; Meera Thomas; Ruchika Goel (Immunologic Research, 2024)

Spectrum of various CNS inflammatory demyelination diseases following COVID-19 vaccinations - Manish Salunkhe; Kamlesh Tayade; Megha Priyadarshi; Vinay Goel; Isha Gulati; Ajay Garg; Rohit Bhatia; M. V. Padma Srivastava (Acta Neurologica Belgica, 2024)

Evaluation of low-cost oxygen carriers for biomass chemical looping gasification - Avishek Goel; Arnold Ismailov; Elyas M. Moghaddam; Chao He; Jukka Konttinen (Chemical Engineering Journal, 2023)

Site-specific characterisation of hydrogeological parameters for low-level solid radioactive waste disposal facility at Tarapur, India - Shelly Goel; Manish Chopra; Aditi C Patra; Faby Sunny; G Ganesh; R B Oza; M S Kulkarni (Journal of Earth System Science, 2023)

Consumer attitudes and perceptions towards chilled ready-to-eat foods: a multi-national study - Nada Smigic; Sibel Ozilgen; Vicente M. Gómez-López; Sandra María Osés; Zorana Miloradovic; Biljana Aleksic; Jelena Miocinovic; Sonja Smole Možina; Ajda Kunčič; Raquel Guiné; João Carlos Gonçalves; Joanna Trafialek; et al. (Journal of Consumer Protection and Food Safety, 2023)

Random distribution of nucleotide polymorphism throughout the genome of tomato-infecting begomovirus species occurring in India: implication in PCR based diagnosis - Pradeep Kumar; Praveen Kumar Oraon; Pragati Yadav; Anirban Roy; Shailendra Goel; M. Krishna Reddy; Sunil Kumar Mukherjee; Bikash Mandal (VirusDisease, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Trend analysis of hydro-meteorological parameters in the Jhelum River basin, North Western Himalayas - Sheikh Umar; M. A. Lone; N. K. Goel; Mohammad Zakwan (Theoretical and Applied Climatology, 2022)

The Built Environment and Health in Low- and Middle-Income Countries: a Review on Quantitative Health Impact Assessments - M. Thondoo; R. Goel; L. Tatah; N. Naraynen; J. Woodcock; Mark Nieuwenhuijsen (Current Environmental Health Reports, 2022)

Modeling of peak discharges and frequency analysis of floods on the Jhelum river, North Western Himalayas - Sheikh Umar; M. A. Lone; N. K. Goel (Modeling Earth Systems and Environment, 2021)

Modeling of annual rainfall extremes in the Jhelum River basin, North Western Himalayas - Sheikh Umar; M. A. Lone; N. K. Goel (Sustainable Water Resources Management, 2021)

Correction to: Evaluation and ranking of different gridded precipitation datasets for Satluj River basin using compromise programming and f-TOPSIS - Bratati Chowdhury; N. K. Goel; M. Arora (Theoretical and Applied Climatology, 2021)

Evaluation and ranking of different gridded precipitation datasets for Satluj River basin using compromise programming and f-TOPSIS - Bratati Chowdhury; N. K. Goel; M. Arora (Theoretical and Applied Climatology, 2021)

Development of mixed anaerobic culture for degrading high concentrations of chlorophenols - M. Goel; M. Ramesh; J. S. Sudarsan; R. Kanawade; S. Nithiyanantham (International Journal of Environmental Science and Technology, 2020)

Novel candidates in early-onset familial colorectal cancer - Anne M. L. Jansen; Pradipta Ghosh; Tikam C. Dakal; Thomas P. Slavin; C. Richard Boland; Ajay Goel (Familial Cancer, 2020)

Prediction of upslope movement of Rhododendron arboreum in Western Himalaya - Sri N. S. Veera; Rajendra M. Panda; Mukunda D. Behera; Shailendra Goel; Partha S. Roy; Saroj K. Barik (Tropical Ecology, 2019)

Prediction of Ground Behaviour for Rock Tunnelling - R. D. Dwivedi; R. K. Goel; M. Singh; M. N. Viladkar; P. K. Singh (Rock Mechanics and Rock Engineering, 2019)

Stability of Vaccines - N. Dumpa; K. Goel; Yuhan Guo; H. McFall; Amit Raviraj Pillai; Ashay Shukla; M. A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2019)

5-HT6 receptor agonist and antagonist modulates ICV-STZ-induced memory impairment in rats - Anand M. Bokare; Mandar Bhonde; Rajan Goel; Yogendra Nayak (Psychopharmacology, 2018)

Identification and characterization of Candidatus Phytoplasma trifolii (16SrVI-D) inducing shoot proliferation disease of potato in India - G. P. Rao; A. Mishra; M. K. Mishra; Ashutosh Rao; Sonia Goel (Indian Phytopathology, 2018)

Endocellulase Production by Cotylidia pannosa and its Application in Saccharification of Wheat Bran to Bioethanol - Deepika Sharma; Amit Sud; Saurabh Bansal; Rishi Mahajan; B. M. Sharma; Rajinder Singh Chauhan; Gunjan Goel (BioEnergy Research, 2018)

Mortality associated with candidemia in non-neutropenic cancer patients is not less compared to a neutropenic cohort of cancer patients - G. Goel; M. Chandy; A. Bhattacharyya; S. Banerjee; S. Chatterjee; S. Mullick; S. Sinha; K. Sengupta; K. Dhar; S. Bhattacharya; S. Rudramurthy; A. Chakrabarti (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Development of an efficient, genotype independent plant regeneration and transformation protocol using cotyledonary nodes in safflower (Carthamus tinctorius L.) - V. Patial; R. Krishna; G. Arya; V. K. Singh; M. Agarwal; S. Goel; A. Jagannath; A. Kumar (Journal of Plant Biochemistry and Biotechnology, 2016)

Response of indigenously developed bacterial consortia in progressive degradation of polyvinyl chloride - Mohammad S Anwar; Anil Kapri; Vasvi Chaudhry; Aradhana Mishra; Mohammad W. Ansari; Yogesh Souche; Chandra S. Nautiyal; M. G. H. Zaidi; Reeta Goel (Protoplasma, 2016)

Numerical study of a buoyant plume from a multi-flue stack into a variable temperature gradient atmosphere - Ratna Kishore Velamati; M. Vivek; K. Goutham; G. R. Sreekanth; Santosh Dharmarajan; Mukesh Goel (Environmental Science and Pollution Research, 2015)

Effect of Allelic Variation in Triticin on Bread- and Chapati-Making Qualities of Wheat (Triticum aestivum) - Sonia Goel; Meenal Rathore; Sapna Grewal; Neha Jain; Binay K. Singh; Arvind K. Ahlawat; Anju M. Singh; Pradeep K. Singh; Nagendra K. Singh (Agricultural Research, 2015)

Assessment of genetic diversity in Indian rice germplasm (Oryza sativa L.): use of random versus trait-linked microsatellite markers - SHEEL YADAV; ASHUTOSH SINGH; M. R. SINGH; NITIKA GOEL; K. K. VINOD; T. MOHAPATRA; A. K. SINGH (Journal of Genetics, 2013)

Curative effect of Terminalia chebula extract on acetic acid-induced experimental colitis: role of antioxidants, free radicals and acute inflammatory marker - M. K. Gautam; Shalini Goel; R. R. Ghatule; A. Singh; G. Nath; R. K. Goel (Inflammopharmacology, 2013)

Molecular Characterization of Vibrio cholerae O1 Reveals Continuous Evolution of Its New Variants in India - M. Jain; K. S. Kushwah; P. Kumar; A. K. Goel (Indian Journal of Microbiology, 2013)

Surface Plasmon Resonance Biosensor for Detection of Bacillus anthracis, the Causative Agent of Anthrax from Soil Samples Targeting Protective Antigen - N. Ghosh; G. Gupta; M. Boopathi; V. Pal; A. K. Singh; N. Gopalan; A. K. Goel (Indian Journal of Microbiology, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Molecular characterization of a new isolate of phytoplasma associated with malformation and twisting of floral spikes of Gladiolus in India - S. K. Raj; S. K. Snehi; M. S. Khan; M. H. Asif; S. K. Bag; R. K. Roy; A. K. Goel (Journal of General Plant Pathology, 2010)

In vitro morphogenesis in leaf sheath explants of sugarcane hybrid var. CoS 99259 - Y. Goel; V. P. Singh; M. Lal; M. L. Sharma (Sugar Tech, 2010)

Limitation of 90 m SRTM DEM in drainage network delineation using D8 method—a case study in flat terrain of Bangladesh - M. M. Rahman; D. S. Arya; N. K. Goel (Applied Geomatics, 2010)

Variation of ambient SO2 over Delhi - A. Datta; T. Saud; A. Goel; S. Tiwari; S. K. Sharma; M. Saxena; T. K. Mandal (Journal of Atmospheric Chemistry, 2010)

Molecular characterization of Vibrio cholerae outbreak strains with altered El Tor biotype from southern India - A. K. Goel; M. Jain; P. Kumar; S. C. Jiang (World Journal of Microbiology and Biotechnology, 2010)

Virulence profile and clonal relationship among the Vibrio cholerae isolates from ground and surface water in a cholera endemic area during rainy season - A. K. Goel; M. Jain; P. Kumar; D. V. Kamboj; L. Singh (Folia Microbiologica, 2010)

Assessment of environmental benefits of flyover construction over signalized junctions: a case study - S. K. Goyal; Sangita Goel; S. M. Tamhane (Environmental Monitoring and Assessment, 2009)

Transfer of leaf rust and stripe rust resistance from Aegilops umbellulata Zhuk. to bread wheat (Triticum aestivum L.) - Parveen Chhuneja; Satinder Kaur; R. K. Goel; M. Aghaee-Sarbarzeh; M. Prashar; H. S. Dhaliwal (Genetic Resources and Crop Evolution, 2008)

Mapping of adult plant stripe rust resistance genes in diploid A genome wheat species and their transfer to bread wheat - Parveen Chhuneja; Satinder Kaur; Tosh Garg; Meenu Ghai; Simarjit Kaur; M. Prashar; N. S. Bains; R. K. Goel; Beat Keller; H. S. Dhaliwal; Kuldeep Singh (Theoretical and Applied Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Podophyllum hexandrum modulates gamma radiation-induced immunosuppression in Balb/c mice: Implications in radioprotection - H. C. Goel; H. Prakash; A. Ali; M. Bala (Molecular and Cellular Biochemistry, 2007)

Operation analysis of a reservoir in GIS environment using remote sensing inputs - M. K. Goel; P. Kumar; S. K. Jain; R. S. Tiwari (International Journal of Remote Sensing, 2007)

Immunological Biosensor for Detection of Vibrio cholerae O1in Environmental Water Samples - M. K. Sharma; A. K. Goel; L. Singh; V. K. Rao (World Journal of Microbiology and Biotechnology, 2006)

Radioprotective mechanism of Podophyllum hexandrum during spermatogenesis - N. Samanta; K. Kannan; M. Bala; H. C. Goel (Molecular and Cellular Biochemistry, 2004)

Brackish water subirrigation for vegetables - R. M. Patel; S. O. Prasher; P. K. Goel; C. A. Madramootoo; R. S. Broughton (Irrigation and Drainage, 2003)
As freshwater resources for irrigation are being depleted rapidly, recent emphasis has been on the development of nonconventional water sources: reuse of agricultural drainage water, use of industrial or municipal wastewater, and use of brackish water for irrigation. Experiments conducted in field lysimeters over three seasons sought to investigate the feasibility of using brackish water for growing moderately sensitive crops. Brackish waters, with salinity levels of 1, 5 and 9 dS m −1 , were used. In 1993 the effects of a factorial combination of three subirrigation water salinity levels, two water table depths and four NPK fertilizer combinations on salt buildup in an initially nonsaline soil and on green pepper ( Capsicum annuum L.) performance were assessed. A gradual increase in soil solution salinity (EC sw ) from the water table to the soil surface was evident; however, throughout the growing season, the EC sw did not reach a level that could seriously damage the crop. There was no significant difference in pepper yields due to either salinity of subirrigation water or water table depth. In 1994, two potato ( Solanum tuberosum L.) cultivars were grown in the soil, which was salinized with 3.5 dS m −1 water before planting tubers. The salt buildup pattern was similar to that observed in 1993; however, the EC sw levels were higher in 1994 due to the higher initial soil salinity. Moreover, a decrease in EC sw was observed near the water table in lysimeters subirrigated with 1 dS m −1 water. For both cultivars, no significant difference in tuber yield was observed due to either water table depth or subirrigation water salinity. In 1995, three potato cultivars were grown in a nonsaline soil as well as a soil presalinized with 2 dS m −1 water. In the topsoil layer, higher rate of increase in EC sw was observed in the saline soil compared to the nonsaline soil. No significant difference in total tuber yield was observed due to either the initial soil salinity levels or subirrigation water salinity levels. Brackish water with salinity levels of up to 9 dS m −1 , when applied through subirrigation, could be used to successfully produce green peppers and potatoes under semiarid to arid conditions. Copyright © 2002 John Wiley & Sons, Ltd.

Individual and combined effect of (±)-α-hydrastine and (±)-β-hydrastine on spore germination of some fungi - M. Goel; U. P. Singh; R. N. Jha; V. B. Pandey; M. B. Pandey (Folia Microbiologica, 2003)

Prophylactic oophorectomy in Ontario - L. Elit; B. Rosen; V. Goel; L. McLaughlin; M. K. F. Fung; J. Shime; S. Narod (Familial Cancer, 2001)

Evidence for new nuclear and mitochondrial genome organizations among high-frequency somatic embryogenesis-derived plants of allotetraploid Coffea arabica L. (Rubiaceae) - V. Rani; K. P. Singh; B. Shiran; S. Nandy; S. Goel; R. M. Devarumath; H. L. Sreenath; S. N. Raina (Plant Cell Reports, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Genotypic detection of mutations in rifampicin resistant clinical isolates ofMycobacterium tuberculosis - L. M. Srivastava; Madhu Khanna; Ashish Goel; R. C. Jain (Indian Journal of Clinical Biochemistry, 1997)

Development of a computer model to predict strains in the individual fibers of a ligament across the ligamentous occipito-atlanto-axial (C0-C1-C2) complex - Vijay K. Goel; Toru M. Yamanishi; Han Chang (Annals of Biomedical Engineering, 1992)